2022
DOI: 10.1111/1744-7917.13047
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the trail pheromone components of the red imported fire ant, Solenopsis invicta Buren

Abstract: Ants use species-specific trail pheromones to coordinate their sophisticated foraging behavior. During the past decades, many trail pheromone components with various structures have been identified in ants, including the red imported fire ant, Solenopsis invicta, a notorious invasive species worldwide. Four compounds, Z,E-(ZEF) and E,E-αfarnesene (EEF), Z,E-(ZEHF) and E,E-α-homofarnesene (EEHF), have been reported as components of S. invicta trail pheromone. However, another study reported an analog of α-farne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…For example, trail pheromones are important for foraging behaviors in ant species. Recently, four trail pheromones, Z , E -α-farnesene (ZEF); E , E -α-farnesene (EEF); Z , E -α-homofarnesene (ZEHF); and E , E -α-homofarnesene (EEHF), were identified in S. invicta , and two of them, ZEF and EEF, mediated the mutualism between ants and aphids [ 41 ]. In addition, the trail pheromones in Myrmicine and Formicine species were identified as farnesene isomers [ 42 , 43 ], suggesting that the mechanism for recognizing trail pheromones may be similar between species.…”
Section: Discussionmentioning
confidence: 99%
“…For example, trail pheromones are important for foraging behaviors in ant species. Recently, four trail pheromones, Z , E -α-farnesene (ZEF); E , E -α-farnesene (EEF); Z , E -α-homofarnesene (ZEHF); and E , E -α-homofarnesene (EEHF), were identified in S. invicta , and two of them, ZEF and EEF, mediated the mutualism between ants and aphids [ 41 ]. In addition, the trail pheromones in Myrmicine and Formicine species were identified as farnesene isomers [ 42 , 43 ], suggesting that the mechanism for recognizing trail pheromones may be similar between species.…”
Section: Discussionmentioning
confidence: 99%
“…50 In this study, the other 12 terpenoids but not the other two compounds were found to be significantly enriched in the field at high temperatures, which emphasized that the response compounds varied with plant species. However, (trans, trans)-α-farnesene was reported to play a role in recruiting natural enemies to defend against red ants (Formica aquilonia), 51 while Souleyre et al 52 demonstrated that reduced (trans, trans)-α-farnesene is associated with decreased disease initiation by three important postharvest pathogens. In this study, the citrus miner insect induced an increase in (trans, trans)-α-farnesene production, whereas the level of this compound decreased after infection with the citrus canker pathogen.…”
Section: Commonly Changed Volatile Terpenoids Under Various Stressors...mentioning
confidence: 99%
“…Alarm pheromones elicit aggression and attack in conspecifics, promote increased movement, gaped mandibles, sting extrusion, trail laying, and aggressive postures (Morgan 2008;Vander Meer et al 2010). Recruitment and trail pheromones from Dufour's gland organize large food retrieval, coordinate foraging and mediate mutualism with aphids (Vander Meer et al 1988, 1990Xu et al 2022). Cuticular hydrocarbons facilitate nestmate and caste recognition (Monnin 2006), and venom defends against intruders and prey (Greenberg et al 2008).…”
Section: Dorsalismentioning
confidence: 99%